Accurate characterizations of material using microwave T-resonator for solid sensing applications - Rammah A. Alahnomi; Z. Zakaria; Zulkalnain Mohd Yussof; Tole Sutikno; H. Sariera; Amyrul Azuan Mohd Bahar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The topic of microwave sensors in enclosures is one of the most active areas in material characterization research today due to its wide applications in various industries. Surprisingly, a microwave sensor technology has been comprehensively investigated and there is an industry demand for an accurate instrument of material characterization such as food industry, quality control, chemical composition analysis and bio-sensing. These accurate instruments have the ability to understand the properties of materials composition based on chemical, physical, magnetic, and electric characteristics. Therefore, a design of the T-resonator has been introduced and investigated for an accurate measurement of material properties characterizations. This sensor is designed and fabricated on a 0.787 mm-thickness Roger 5880 substrate for the first resonant frequency to resonate at 2.4 GHz under unloaded conditions. Various standard dielectric of the sample under test (SUT) are tested to validate the sensitivity which making it a promising low-cost, compact in size, ease of fabrication and small SUT preparation for applications requiring novel sensing techniques in quality and control industries.